An exploration of classroom learning environment in college physics in a Philippine technical school - Rivera, Elizabeth R. (Animo Repository, 2003)
This study sought to determine the learning environment factors associated with student interest and perceived competencies of 190 students in FEATI University during the second semester of school year 2002-2003. The study made use of the standardized Cultural Learning Environment (CLEQ) Questionnaire (Fisher and Waldrip, 1998) to determine the cultural factors comprising the classroom learning environment in Physics as perceived by the students. The students’ level of interest and perceived competencies in Physics was measured by adapting the Perception of Science Classes Survey (PSCS) Questionnaire (Kardash and Wallace, 2000). The researcher made use of frequency count, weighted mean, rank and standard deviation to describe the respondents’ perceptions of their Physics class as well as their level of interest and perceived competencies in the subject. The Pearson Product-Moment Correlation was used to test if significant relationship exists between the aforecited variables. Furthermore, it is examined if there were significant differences in the students’ level of interest and perceived competencies in Physics when they were grouped according to course, year level and type of high school graduated. Using the Analysis of Variance (ANOVA) did this. A stepwise regression was conducted to evaluate if the cultural learning environment factors, singly or in combination, affect the students’ level of interest and perceived competencies in Physics. Results of the study revealed that 1) the respondent Physics classes is more likely to collaborate, challenge their teachers, use modeling in learning Physics, and perceive what they learn in the class as matching their learning at home; 2) the respondents have a generally low level of interest and perceived competencies in Physics; 3) there is no significant differences in the students’ level of interest in Physics when grouped according to course, year level and type of high school graduated; 3) there is significant differences in the students’ perceived competencies in Physics when grouped according to course and year level; 4) there is significant relationship between the different dimensions of cultural learning environment and the students’ level of interest in Physics , except in terms of collaboration; 5) there is a significant relationship between gender equity, collaboration and congruence factors and perceived competencies in Physics; 6) congruence and deference environment factors, singly or in combination, do affect the students’ level of interest in Physics; 7) collaboration and competition are the two factors that affect, singly or in combination, the perceived competencies of respondents in Physics.